“Echoes over the lake”: Literary translation and the paratext - Gonçalves, Davi Silva (Revista Letras Raras, 2023)
DOI: https://dx.doi.org/10.35572/rlr.v6i3.868 The problem investigated by this article regards the reconstruction of laughter through literary translation, whose “unnatural” but essential interpretative status is deemed by many critics inherently detrimental to the very emergence of comic effects. My overall context, therefore, is that of humorous discourse, as I set off from the premise that humour is one of the first glimpses of how complex human interactions are. But, besides humour, the locale of this study is also that of literary translation; as my reflection upon the emergence of laughter in Leacock’s novel Sunshine sketches of a little town (1912) is also accompanied by my proposal to translate its comic effect. Theretofore, my choice has been that of including a para-text to the Brazilian version of the narrative, where I would elaborate, through footnotes, on the exaggerated inter-textual analogies set in motion by Leacock’s (1912) narrator. My hypothesis is that such references are crucial for the exaggerated tone that is loaded in the narrator’s assertions, as they serve to the incongruous approximation between the town described in the story (the fictional Mariposa) to cities, peoples, institutions, and events of global impact.